The guided use of an e-health tool to strengthen health literacy. A pilot study in a multicultural diabetes population in a primary care clinic in Brussels - Lien Mertens; Harrie Dewitte; Lieve Seuntjens; Rita Vanobberghen; Bert Aertgeerts (Elsevier, 2022)
Objectives: We aimed to investigate whether the use of an e-health tool, guided by a healthcare provider, can improve health literacy (HL) in primary care. Methods: We set up a longitudinal prospective cohort study in a primary care clinic in Brussels. Diabetes patients were invited to participate in two study consultations with a trained healthcare provider, in which an e-health tool was introduced. The Health Literacy Questionnaire (HLQ) was used to evaluate HL before (n = 59) and after intervention (n = 41). The data were analysed within SPSS, Version 26. Additionally, impressions and experiences of both patients and healthcare providers were collected throughout the different phases of the study. Results: Patients feel significantly stronger in finding good health information after intervention (p = 0.041), with relatively stronger progress for the subgroup with weaker digital skills (p = 0.029). Participants also declare understanding health information better after intervention (p = 0.050). Specifically, the lower educated participants feel reinforced to correctly evaluate and assess health information and come closer to the skill level of the higher educated patients after intervention. The relationship with the healthcare provider was also more markedly enhanced within the group of the lower educated (p = 0.008; difference between higher and lower educated), which could strengthen self-management in the long run. Conclusions: The guided use of an e-health tool in primary care strengthens various patient HL skills. Most particularly the skills "the ability to find good health information" and "understand health information well enough to know what to do" are reinforced. Moreover, patient populations with lower HL, such as the lower educated and lower digitally skilled, show a greater learning potential. Innovation: Our results offer further proof for the learnable and flexible nature of HL, and show that even a small e-health intervention, in a very diverse patient population, can produce significant, positive effects on HL. These results need to be considered as promising, and a motivation for further investments in more widely accessible e-health tools to further improve HL at population level and to bridge health differences.